(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
The Dja Biosphere Reserve is home to immense natural resources. Increasing poaching and other human activities like shifting cultivation and industrial agriculture are major problems in this area. This study addresses the need to explore attitude and perception of local residents toward wildlife and conservation. Questionnaires surveys and field observations were used in data collection. A total of 400 people was conveniently selected in 16 villages from October to December 2015. Data analysis relied mainly on factor analysis and structural equation modelling in SPSS 21 and Smart-PLS software. The main findings indicate a significant positive relationship between wildlife education, community wildlife sensitization and the local attitude on community involvement in conservation, which in turn have a strong and positive significant impact on the perception of the local people towards wildlife and conservation. Moreover, the perception of local people has a significant positive impact on the level of discipline towards wildlife and conservation. The results also suggest that local people perception index is not one-dimensional but can be considered as a three-dimensional construct affected by intention, wildlife threat and community involvement. Strategies aiming to change the perception of local people toward wildlife and conservation therefore need integrated approaches. This research points the involvement of local communities in wildlife management as an essential strategy to shape positive perception toward wildlife. Anti-poaching strategies will be easier if local people had a good perception towards wildlife and conservation. Wildlife education and sensitization are also essential in any conservation strategy, as they are key drivers of positive perception toward wildlife and conservation.